An Anthropologist’s Apprenticeship: Diamond Jenness’ Papuan and Arctic Fieldwork - Richling, Barnett (Culture, 1989)
Diamond Jenness (1886-1969) was a major figure in Canadian anthropology during the first half of the century. This paper provides some biographical-historical details of his early career, concentrating on major fieldwork in Papua New Guinea in 1912, and in northern Alaska and Canada’s Coronation Gulf region between 1913 and 1916. Relying mainly on Jenness’ unpublished field diaries and personal correspondence, it identifies links between his work in the south Pacific and the Arctic, and examines the source of prominent themes that found expression during his later professional career. Particular attention is given to the three years Jenness served as a member of Stefansson’s Canadian Arctic Expedition, and to his role in accomplishing the Expedition’s anthropological objectives.